BUDIDAYA PADI (Oryza sativa L) DI DESA TANGKAS KECAMATAN MARTAPURA BARAT KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Bahrun Bahrun (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
Research executedding to know paddy farming activity if is sighted from teknis's aspect, and of aspect economicing to know amount and it big cost, acceptance and income of Silvan paddy farming Tangkas. Total farmer that do paddy farming activity varietas Siam at Silvan Tangkas as much 271 person. Take at random simple( Simple Random is Sampling ) as much 10 % (27 person) of all population. Acquired production average as big as 2.015,74 kg / farmers or as big as 3.101,14 kg / ha (3,10 tons/ha). Acceptance average as big as Rp. 11.086.574,07 / farmers or as big as Rp. 17.056.267,81 / ha. income average as big as Rp. 6. 788. 924,60 /farmers or Rp. 10. 444. 499,39/ ha.